Richard W. Pfaff, The Liturgy in Medieval England: A History (2009) - Buckley, Ann (Journal of the Society for Musicology in Ireland, 2012)
A review of Richard W. Pfaff, The Liturgy in Medieval England: A History (Cambridge: Cambridge University Press: 2009), ISBN 978-0-521-80847-7.